Pengaruh Promosi, Kualitas Produk dan Kepercayaan Belanja Online terhadap Keputusan Pembelian Produk Fashion pada Situs Lazada.co.id (Studi Pada Mahasiswa Universitas Kanjuruhan Malang) - Rohani Wona; Iva Nurdiana Nurfarida; Candra Wahyu Hidayat (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This study aims to measure the effect of promotion variables, product quality, and trust in purchasing decisions. The object of this research is Malang Kanjuruhan University students who have shopped online for fashion products on lazada.co.id. The type of research used is quantitative research. This research uses rendom sampling technique with a sample size of 112 respondents, where the data used are primary data. The analysis technique used is multiple linear regression analysis and data analysis by conducting validity and reliability testing, classic asumi test, coefficient of determination (R2) and hypothesis testing. Based on statistical data analysis, the items in this study are valid and reliable. In testing classic assumptions, free regression and ultikolonieritas odel, heteroscedasticity does not occur, and normally distributed. The biggest variable is the promotion variable by 0.333, while the smallest variable is the variable, namely the trust variable by 0.290, and the product quality variable by 0.257. Y = 0.453 + 0.333 + 0.257 + 0.290+ e. From the results of multiple regression analysis on alpha 5%, Fcount was 59,756 while Ftable was 1,734 so from the calculation it could be seen that Fcount ≥ Ftable so that H1 was accepted HO was rejected. Promotion variable (x1) shows a significant value of t of 0,000 ≤ 0.05 meaning there is an influence of the promotion variable (x1) on the purchase decision variable (y) thus it can be concluded that H2 received by HO is rejected. The product quality variable (x2) shows a significant value of t of 0.001 ≤ 0.05 meaning there is an influence of the product quality variable (x2) on the purchase decision variable (y) thus it can be concluded that H3 is accepted as HO rejected. The trust variable (x3) shows a significant t of 0,000 ≤ 0.05 meaning there is an influence of the trust variable (x3) on the decision of furniture (y) thus it can be concluded that H4 is received and HO is rejected.